2017
DOI: 10.1155/2017/7674594
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Based DDoS HTTP Attack Detection Using Covariance Matrix Approach

Abstract: In this era of technology, cloud computing technology has become essential part of the IT services used the daily life. In this regard, website hosting services are gradually moving to the cloud. This adds new valued feature to the cloud-based websites and at the same time introduces new threats for such services. DDoS attack is one such serious threat. Covariance matrix approach is used in this article to detect such attacks. The results were encouraging, according to confusion matrix and ROC descriptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…The final class is the traditional, incremental learning model that is being updated to detect other types of cyber-attacks. And IDTL classified with distance in the testing phase by recognizing the values of the training phase, similar to the research of Aborujilah and Musa [45] which has the same high efficiency.…”
Section: Discussionmentioning
confidence: 81%
“…The final class is the traditional, incremental learning model that is being updated to detect other types of cyber-attacks. And IDTL classified with distance in the testing phase by recognizing the values of the training phase, similar to the research of Aborujilah and Musa [45] which has the same high efficiency.…”
Section: Discussionmentioning
confidence: 81%
“…Aborujilah and Musa [31] introduced cloud-based detection of HTTP DDoS by using statistical approach with the covariance matrix. e detection introduced two algorithms known as training and testing to recognise a di erent type of HTTP ooding attack based on attack behaviour.…”
Section: Recent Detection Methods For Http Ddos Attackmentioning
confidence: 99%
“…is review also found that a few researchers evaluated their proposed work by using simulation software [30][31][32]36]. On the other hand, some [2,19,28,[33][34][35] performed real experiments to evaluate their outcomes and found only one study [37] assessed their work by using simulation software and experimental works.…”
Section: Evaluation Methodmentioning
confidence: 99%
See 2 more Smart Citations